CUMS Remembered / Souvenirs de la SMUC - Beckwith, John (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1999)
On the occasion of his induction as a lifetime honorary member of the Canadian University Music Society, the Dean of Canadian composers, John Beckwith, offers a personal reflection on the triumphs and vicissitudes across more than thirty years of the Society. From its 1964 founding as a network of music deans and directors under the acronym CAUSM, through its metamorphosis into a learned society in the 1980s, to its present day hybrid form, CUMS is remembered—with affection and whimsy—as an agent in development of the Canadian music establishment.